Legal regulation of surrogacy parentage determination in China - You, Wenting; Feng, Jun (Frontiers in Psychology, 2024)
Unlike natural conception and other assisted reproductive technologies, surrogacy involves three crucial factors: family legislation, family ethics, and reproductive technology. This makes the determination of parentage in surrogacy more complex. In China, surrogacy is completely prohibited by law.However, this prohibition has not diminished the interest in discussions around the family ethics, order, and relationships affected by surrogacy. In practice, disputes over parentage and child custody arising from surrogacy urgently need resolution through judicial practice. The current legal framework in China lacks clear regulations to address the complexities of surrogacy, leading to numerous unresolved disputes. To address this issue, it is advisable for China to enact clear legislative measures to govern parent-child relationships in surrogacy cases. This paper presents legislative recommendations for regulating surrogacy in China, with the hope that the judicial interpretations of the Supreme People's Court of China can provide clear legal regulations on surrogacy during revisions.